Transformative pedagogical practices: Improving students’ listening comprehension through video-based activities - Diana Anggraeni; Noor Hasnoor Mohamad Nor; Rizky Arif Afandi; Rodiawan (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2026)
Studies have suggested that video-based listening activities using visual and auditory cues can be an effective learning tool to help students having issues with listening skills. This study examined the impact of video-based listening exercises on the listening comprehension skills of 21 fifth-grade students, with a focus on the identification of specific facts. The study employed an action research method, incorporating pre- and post-tests, Likert-scale questionnaires, and Focus Group Discussion (FGD) talks to evaluate students' progress and perceptions. The intervention was conducted over four weeks through four classroom sessions. The results showed that the intervention made a significant difference in how well pupils understood what they heard. The score on the pre-intervention test went from 8.79 to 9.37 out of 10 on the post-test, demonstrating the improvement of students’ understanding on fast speech and small details. Students reported that video-based tasks were fun and engaging and the audio-visual materials enhanched their focus, confidence, and enjoyment in learning. The results show that video-based listening exercises are effective for EFL learners and should be used more widely to help them develop their listening abilities and improve language learning experiences.